3D finite element modeling of bond-controlled behavior of steel and basalt FRP-reinforced concrete square bridge columns under lateral loading. (20th May 2016) - Ibrahim, Arafa M.A.; Fahmy, Mohamed F.M.; Wu, Zhishen
Abstract: Bond between reinforcing bars and concrete plays an important role in controlling the structural performance of reinforced concrete (RC) structures. The main objective of this study was to create and execute a detailed three dimensional (3D) finite element (FE) model evaluating the structural performance of fiber reinforced polymer (FRP)-steel RC (FSRC) bridge columns and considering the effect of several bond conditions between FRP bars and concrete. Hence, bond behavior of basalt FRP (BFRP) bars with different surface conditions was firstly discussed in comparison with ribbed steel bars. After that, results of the created 3D FE models for FSRC columns reinforced with BFRP bars having different bond conditions were validated in the light of results of four columns experimentally tested under the combined effect of constant axial load and cyclic lateral loading. Ultimately, a parametric study was conducted to find out the effect of different bond conditions of FRP bars on the structural performance of FSRC columns. The numerical results showed that response of FSRC columns to lateral loading is dependent on bond conditions between FRP bars and the surrounding concrete: characteristics of bond–slip relationship of FRP bars could be adopted as design parameters controlling the behavior of FSRC columns. Failure mode, lateral strength, post-yield stiffness ratio, ductility at the peak lateral strength and at failure are all depend on the bond parameters of FRP bars. However, FRP bond parameters did not show a pronounced impact on the column elastic stiffness.